Intrinsic and Extrinsic Motivation on Job Satisfaction and Nurse Performance at the Hospital - Nursalam . (Journal of Global Pharma Technology, 2016)
Introduction: Poor motivation and limited health services-oriented are reducing job satisfaction, which may affect the quality of nurse performance. The aim of this study to analyze the intrinsic and extrinsic motivation on job satisfaction and nurse performance at the hospital. Methods: The study was explanatory research with a quantitative approach. The sample was 295 respondents from maternal and child hospital nurses. The sampling method is proportional random sampling area, the number of samples determined using the Slovin’s formula. The analysis technique used the Structural Equation Model with PLS Warp analysis tools. Results: Predisposing factor (intrinsic and extrinsic motivation) significantly the nursing job satisfaction. The relationship between intrinsic and extrinsic motivation with job satisfaction and nursing performance was significant. Conclusion: Integration of self-esteem with extrinsic motivation has a good effect on job satisfaction which in increased nursing performance. However, it was important for hospital management to motivate their nurse through intrinsic and extrinsic motivation continuously.Keywords: Intrinsic motivation, Extrinsic motivation, Job satisfaction, Nurse performance.